Environmental and human health challenges of industrial livestock and poultry farming in China and their mitigation. (October 2017) - Hu, Yuanan; Cheng, Hefa; Tao, Shu
Abstract: Driven by the growing demand for food products of animal origin, industrial livestock and poultry production has become increasingly popular and is on the track of becoming an important source of environmental pollution in China. Although concentrated animal feeding operations (CAFOs) have higher production efficiency and profitability with less resource consumption compared to the traditional family-based and "free range" farming, they bring significant environmental pollution concerns and pose public health risks. Gaseous pollutants and bioaerosols are emitted directly from CAFOs, which have health implications on animal producers and neighboring communities. A range of pollutants are excreted with the animal waste, including nutrients, pathogens, natural and synthetic hormones, veterinary antimicrobials, and heavy metals, which can enter local farmland soils, surface water, and groundwater, during the storage and disposal of animal waste, and pose direct and indirect human health risks. The extensive use of antimicrobials in CAFOs also contributes to the global public health concern of antimicrobial resistance (AMR). Efforts on treating the large volumes of manure generated in CAFOs should be enhanced (e.g., by biogas digesters and integrated farm systems) to minimize their impacts on the environment and human health. Furthermore, the use of veterinary drugs and feed additives in industrial livestock and poultry farming should be controlled, which will not only make the animal food products much safer to the consumers, but also render the manure more benign for treatment and disposal on farmlands. While improving the sustainability of animal farming, China also needs to promote healthy food consumption, which not only improves public health from avoiding high-meat diets, but also slows down the expansion of industrial animal farming, and thus reduces the associated environmental and public health risks. Graphical abstract: Highlights: Industrial livestock and poultry production has undergone rapid expansion in China. Animal farms and animal waste release a wide range of pollutants to the environment. These pollutants negatively impact the environment and pose risks to human health. Use of veterinary drugs and feed additives in animal farming should be controlled. Efforts are needed to improve the sustainability of China's animal farming practices.